2012
DOI: 10.12697/poa.2012.21.11
|View full text |Cite
|
Sign up to set email alerts
|

Female pelvis types and age differences in their distribution

Abstract: The aim of this study was a statistics-based exploration of a typology of the female pelvis. The research sample included 172 females aged from 18 to 69. For measurements, the three dimensional CT images of pelvis were used. A cluster analysis was performed on anteroposterion and transverse diameters of the pelvic inlet and the midplane. The results revealed three clusters representing gynecoid, "narrow", and intermediate types of female pelvis. The distribution of pelvic types in age groups indicates a tenden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Our study had a slightly lower mean value for both the anteroposterior (12.85±1.0 cm) and transverse dimensions (13.66±1.07 cm). 9 Our Free Full Text are Available at www.jnma.com.np study showed a slightly lower percentage of gynaecoid pelvis than the study conducted in the Department of Radiology, Cumhuriyet University, on multiparous women which resulted in 47.8% of the gynaecoid pelvis. Anteroposterior and transverse diameters were 11.64±8.0 cm and 14.04±5.7 cm respectively.…”
Section: Discussionmentioning
confidence: 68%
“…Our study had a slightly lower mean value for both the anteroposterior (12.85±1.0 cm) and transverse dimensions (13.66±1.07 cm). 9 Our Free Full Text are Available at www.jnma.com.np study showed a slightly lower percentage of gynaecoid pelvis than the study conducted in the Department of Radiology, Cumhuriyet University, on multiparous women which resulted in 47.8% of the gynaecoid pelvis. Anteroposterior and transverse diameters were 11.64±8.0 cm and 14.04±5.7 cm respectively.…”
Section: Discussionmentioning
confidence: 68%
“…The pelvic type is de ned by APD (anterior-posterior diameter) and TD (transverse diameter) [8] [17], therefore our hypothesis aims to nd a correlation between APD and a chosen external dimension in the sagittal plane, and between TD and a chosen external dimension in the transverse plane. As the birth canal geometry changes along the sagittal plane, we address the upper part (inlet), the middle part and the lower part (outlet)…”
Section: Methodsmentioning
confidence: 99%
“…Maternal anthropometric measures as maternal height, foot length, head circumference and Michaelis transverse diameter might help in detecting risk of CPD [26]. Younger females have narrow pelvis more often than older females [17].…”
Section: Introductionmentioning
confidence: 99%